A case study: Comparison of disinfection by-product formations between LEED-certified and non-certified buildings. (December 2022) - Kalan, Duygu; Ozbek, Mehmet Egemen; Omur-Ozbek, Pinar; Dooley, Gregory
Abstract: In a few studies focusing on premise plumbing, water quality parameters were compared between LEED-certified and non-certified buildings. However, in those studies, the building characteristics were different, which can cause variations in comparison attempts. This study's purpose is to identify the effects of building type on premise plumbing water quality. For this purpose, temperature, pH, free chlorine residuals, total organic carbon, and trihalomethanes (THMs) were sampled from four drinking fountains of a combined LEED-certified and non-certified building. Although some influential factors on water quality (e.g., location of buildings, distributed water quality) were isolated for a better comparison, variations in parameters and total THMs were observed resulting from the plumbing age differences in the buildings. The findings of this study point out the impacts of the plumbing pipe age on water chemistry and emphasize the consideration of piping age as a factor in water quality comparisons between LEED-certified and non-certified buildings. Highlights: Even though the same quality of water was distributed to the building sides, variations in TTHMs were observed. Premise plumbing affected TTHM formations while the building floor was not influential in their respective building sides. Sequential order sampling should be taken into account in water quality sampling protocols for fountains in the future.